The decision on joint properties in Bengkulu High Religious Court Jurisdiction - Jayusman Jayusman (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
Joint property disputes after divorce at the Religious Courts (PA) under the Bengkulu High Religious Court (PTA) jurisdiction are always equally settled by giving half for each ex-spouse, regardless of the domination in working to earn the properties. The decisions refer to the article 97 of the Compilation of Islamic Law (KHI). The decisions do not fulfill sense of justice regarding the ex-wife participating in earning the living. This library research would like to descriptively analyze the progressive law reviews of the decision related to joint properties with working wives set at some Religious Courts under the Bengkulu High Religious Court jurisdiction in 2016-2019 periods, in the context of reforming the Marriage Law in Indonesia. In drawing conclusions, the data are analyzed by applying progressive law theory. The study shows that Religious Courts’ decisions are not regulated in traditional Islamic law, but they are found in contemporary Islamic law by analogizing them as Shirkah with the division based on the agreement between the parties. In positive law perspective, the joint property division has been determined with each equally get half. In the meantime, from the progressive law perspective in the context of reforming the Indonesian Marriage Law, ex-wives participating in earning living should get a larger portion of joint properties than their ex-husbands, to fulfill the sense of justice. Their portions are decided amicably on the agreements of the parties